Attention, Affect, and Aesthetic Experience - Nielsen, Henrik Kaare (The Nordic Journal of Aesthetics, 2023)
The article suggests a conceptualization of the interrelationship between attention, affect, and aesthetic experience. It supplements classical aesthetic theory by integrating knowledge from neurophysiology, developmental psychology, and psychoanalysis. Furthermore, the article proposes a distinction between a variety of types of affect that are discussed with a view to their potential contribution to elaborating the concept of aesthetic experience in the Kantian tradition and to reflecting different qualities of attention.